Microglia remodeling in the visual thalamus of the DBA/2J mouse model of glaucoma - Jennifer L. Thompson; Shaylah McCool; Jennie C. Smith; Victoria Schaal; Gurudutt Pendyala; Sowmya Yelamanchili; Matthew J. Van Hook (PLoS ONE, 2025)
Microglia are the resident immune cells of the central nervous system and mediate a broad array of adaptations during disease, injury, and development. Typically, microglia morphology is understood to provide a window into their function and microglia have the capacity to adopt a broad spectrum of functional phenotypes characterized by numerous morphologies and gene expression profiles. Glaucoma, which leads to blindness from retinal ganglion cell (RGC) degeneration, is commonly associated with elevated intraocular pressure (IOP) and triggers microglia responses within the retinal layers, at the optic nerve head, and in retinal projection targets in the brain. The goal of this study was to determine the relationship of microglia morphology to intraocular pressure and the loss of RGC output synapses in the dorsolateral geniculate nucleus (dLGN), a RGC projection target in the thalamus that conveys information to the primary visual cortex. We accomplished this by analyzing microglia morphologies in dLGN sections from DBA/2J mice, which develop a form of inherited glaucoma, at 4, 9, and 12 months of age, representing distinct time points in disease progression. Microglia morphology was analyzed using skeletonized Iba1 fluorescence images and fractal analyses of individually reconstructed microglia cells. We found that microglia in older DBA/2J mice adopted simplified morphologies, characterized by fewer endpoints and less total process length per microglia cell. There was an age-dependent shift in microglia morphology in tissue from control mice (DBA/2JGpnmb+) that was accelerated in DBA/2J mice. Measurements of microglia morphology correlated with cumulative IOP, immunofluorescence labeling for complement component C1q, and vGluT2-labeled RGC axon terminal density. Additionally, fractal analysis revealed a clear distinction between control and glaucomatous dLGN, with microglia from ocular hypertensive DBA/2J dLGN tissue showing an elongated rod-like morphology. RNA-sequencing of dLGN showed an upregulation of immune system-related genes. These results suggest that microglia in the dLGN alter their physiology to respond to RGC degeneration in glaucoma, potentially contributing to CNS adaptations to neurodegenerative vision loss.